Pattern of Injuries in Fatal Railroad Accident in Dhaka Medical College Mortuary-An Autopsy Based Study - Chowdhury, Arifuzzaman; Karim, Kh A; Zaman, Parvin Dilara; Ahmed, Farjana; Banik, Shyamal Chandra; Taslim, Sarwat Ara; Rahman, Ferdousi (Journal of Dhaka National Medical College & Hospital, 2021)
Objectives: Objectives of this study are to find out the pattern of injuries presented among the railroad accidents victims along with related causes and to evaluate the present situation of railroad accidents in our country. Material and Methods: This is a retrospective study which was carried out on 100 cases of fatal rail road accidents brought to the mortuary for autopsy in the Department of Forensic Medicine & Toxicology, Dhaka Medical College, during the period from 1st October 2017 to 30th September 2018. Results: A total of 100 post mortem cases were studied. Among these 81% were male and 19% were female. Highest incidence of railroad accident was observed among the age group 21 to 40yrs (48%), followed by 41 to 60yrs (36%),0 to 20yrs (11%) and above 60 (5%). Regarding religion almost all cases were Muslim (92%) whereas 5% were unknown and 3% were Hindu. Among these 55(55%) dead bodies were identified and 45(45%) cases were unidentified. The victims of fatal railroad related deaths mainly succumbed to head injury (71%) followed by injury to thoraco-abdominal organs (15%), multiple injuries (11%) and septicemia (3%). Regarding injury pattern in different parts of the body, 100% victims had multiple abrasion and bruises all over the body, fracture were present in (87%) cases, (67%) victims had laceration in different parts of body, (47%) had injury to different organ, (5%) victims had decapitation, (5%) victims had amputation of limbs. Conclusion: It can be concluded from the present study that accidental railway deaths in future can be reduced by implementing safety measures such as improved integrated surveillance system and safety engineering techniques, reduced public access to railway tracks by strict vigil, security measures, and better law enforcement at stations. J. Dhaka National Med. Coll. Hos. 2021; 27 (02): 22-25